Foramen Magnum Stenozu ve Atlantooksipital Dislokasyonu Olan Bir Mukopolisakkaridozlu Olguda Anestezi Yönetimi - Gündüz, Ergün; Can, Halil (Nöroşirürji Nadir Vaka Sunumları, 2024)
Mukopolisakkaridoz (MPS), lizozomal depo hastalıkları grubuna ait, nadir görülen genetik bozuklukdur. Foramen magnum stenozu ve atlantooksipital dislokasyonu olan Mukopolisakkaridoz olgusunun anestezi ve cerrahi yönetimi dikkatli ve özverili olmalıdır. Standart monitörizasyon sonrası anestezi indüksiyonu yapıldı. Videolaringoskopi ile entübe edildi. Endotrakeal entübasyon, kapnograf değeri görülmesi ile doğrulandı. Sevofluran ile anestezi idamesi sağlandı. Verilen sıvı miktarı da 10 ml kg/st verildi. Sol femoral arterde invazif arter monitörizasyonu yapıldı. Sağ femoral venden santral kateter takıldı. Posterior oksipitoservikal enstürmantasyon yapıldı. Cerrahi ve/veya anesteziye bağlı herhangi bir komplikasyon gelişmedi ve sorunsuz olarak ekstübe olarak kontrol ve yakın takip ve tedavi amaçlı yoğun bakıma alındı. MPS hastalarında entübasyon ve genel anestezi yönetimi zorlayıcı olabilir. Havayolu yönetimi zor olduğundan, cerrahi ekip ile anestezi ekibinin yakın iş birliği yapması önemlidir. En uygun yaklaşım, mümkünse fiberoptik entübasyon veya video laringoskopi gibi tekniklerin kullanılmasıdır. Mucopolysaccharidosis (MPS) is a rare genetic disorder belonging to the group of lysosomal storage diseases. The anesthesia and surgical management of a Mucopolysaccharidosis case with foramen magnum stenosis and atlantooccipital dislocation should be careful and dedicated. Anesthesia induction was performed after standard monitoring. He was intubated with video laryngoscopy. Endotracheal intubation was confirmed by capnography values. Anesthesia was maintained with sevoflurane. The amount of fluid administered was also 10 ml kg/hr. Invasive arterial monitoring was performed in the left femoral artery. A central catheter was inserted from the right femoral vein. Posterior occipitocervical instrumentation was performed. No complications related to surgery and/or anesthesia developed and he was extubated without any problems and taken to the intensive care unit for control and close follow-up and treatment. Intubation and general anesthesia management can be challenging in MPS patients. Since airway management is difficult, close cooperation between the surgical team and the anesthesia team is important. The most appropriate approach is to use techniques such as fiberoptic intubation or video laryngoscopy, if available.